2019
DOI: 10.4300/jgme-d-18-00650.2
|View full text |Cite
|
Sign up to set email alerts
|

A Sustainable and Effective Mentorship Model for Graduate Medical Education Programs

Abstract: Background Mentorship models rarely seek generalizability across training programs at the graduate medical education (GME) level. Objective We examined the sustainability and effectiveness of an intervention to increase the number and usefulness of trainee mentorship. Methods A 0.20 full-time equivalent GME faculty adviser position (MD, MEd) implemented mentorship programs in residencies and fellowships. In group 1, 6 GME programs implemented the mentorship strategies prior to 2014, which were used to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…OGP an SNDH each coded the transcripts, discussed to determine the final codes, and categorised them into themes: studentmentor relationship, the meaning of mentorship, valuable mentorship, and model of mentoring. 4,9,11 "Usually, the mentorship only lasts about one to two minutes, so in my opinion it was more of a formality, only asking for a signature for OSCE needs" (P1.3) "He probably didn't have much time; he didn't have enough time for us to vent our complaints like that" (P2.2) "I really want to discuss with him, I hope he will provide a certain time." (P1.10) "Because the impression made was tense and we were afraid of her, so it was a little difficult to be open" (P2.…”
Section: Methodsmentioning
confidence: 99%
“…OGP an SNDH each coded the transcripts, discussed to determine the final codes, and categorised them into themes: studentmentor relationship, the meaning of mentorship, valuable mentorship, and model of mentoring. 4,9,11 "Usually, the mentorship only lasts about one to two minutes, so in my opinion it was more of a formality, only asking for a signature for OSCE needs" (P1.3) "He probably didn't have much time; he didn't have enough time for us to vent our complaints like that" (P2.2) "I really want to discuss with him, I hope he will provide a certain time." (P1.10) "Because the impression made was tense and we were afraid of her, so it was a little difficult to be open" (P2.…”
Section: Methodsmentioning
confidence: 99%
“…The primary advantage of this model is the opportunity to invest deeply in a single, more dedicated relationship [85]. However, because time constraint is a concern for many mentors, it is important to note that weekly and monthly meetings were both shown to have equal success rates, which may make it easier for individual mentors to commit to more mentees [86]. A significant drawback of this method is the lack of diversity offered from a single mentor.…”
Section: Individual Modelmentioning
confidence: 99%
“…In order to ensure high quality of mentors and excellent mentee experience, involvement in a mentorship program must be voluntary, otherwise an advisingtype relationship tends to emerge [86]. While there could be incentives such as dedicated time for mentorship in more academically-oriented institutions, mentors have to be willing to engage for personal reasons.…”
Section: Mentor Responsibilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mentors in medical education (MentorME) is a pilot mentoring program launched by the Department of Anesthesiology, Emory University in January 2020. It incorporates best evidence in building mentorship programs 7 including volunteer faculty participation, ongoing faculty development, access to resources, active mentee choice in the pairing process, mentee and mentor role understanding, facilitated mentoring meetings, and focused relationship reviews. The study reported here was granted exemption by the Emory University Institutional Review Board.…”
Section: Description Of Program Designmentioning
confidence: 99%